Analysis of the treatment protocol for sternotomy wound infection after cardiac surgery - Samuel Terra Gallafrio; Thomaz Tourinho Menezes; Franklin Monaco Filho; Daniel Mamere Alvarez; Tania Mara Varejão Strabelli; Fabio Biscegli Jatene; Rolf Gemperli (Revista Brasileira de Cirurgia Plástica, 2017)
INTRODUCTION: Surgical wound complications after sternotomy in cardiovascular procedures include small dehiscences, mediastinitis, and sternal osteomyelitis. Mediastinitis and sternal osteomyelitis are high-risk complications associated with high rates of morbidity, mortality, and recurrence. Treatment of the most severe cases involves prolonged hospitalization. Moreover, the long-term use of antibiotics during hospitalization and after discharge significantly increases the overall cost of treatment. A recent treatment option involves extensive surgical debridement of the surgical wound, treatment of the wound bed with negative pressure therapy, and closure of the wound with myocutaneous or fasciocutaneous flaps. The advantages of this strategy include improvement of the patient's quality of life, less manipulation and less discomfort for the patient, less burden on staff involved in care, lower rate of infection recurrence, and an overall reduction of treatment morbidity. METHODS: The objective of this study was to conduct a retrospective survey of patients with surgical wound complications who were treated according to a protocol developed and improved by the Heart Institute of the Clinic Hospital of the School of Medicine of the University of São Paulo (Instituto do Coração do Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo-InCor/HC-FM-USP), and who underwent surgery by the same plastic surgeon. The epidemiological profiles and possible indicators of worse prognosis were determined from routine examinations performed on these patients. The medical records of patients treated at InCor/HC-FM-USP who presented with sternotomy infection in 2014 were assessed retrospectively. The analyzed variables included comorbidities, interval between surgical procedures, C-reactive protein (CRP) levels, wound closure procedures, and treatment complications, among others. RESULTS: The data are predominantly descriptive and epidemiological. At least one comorbidity was present in 84% of cases. The mean number of surgical procedures per patient was 2.5, ranging from 1 to 7. The CRP levels decreased in 75% of patients after the first surgical procedure, and the mortality rate was 17%. CONCLUSION: The standardized method adopted significantly decreased the overall mortality and the rates of recurrence and readmission. Indicators of worse prognosis, including CRP levels and the leukogram, were identified at the time of diagnosis and initiation of the treatment protocol.